Hasil Bongkaran Perkerasan Jalan sebagai Bahan Lapis Fondasi Jalan Raya - Widodo, Sri; Harnaeni, Senja Rum; Hakim, Lukman (Department of Civil Engineering, Diponegoro University, 2013)
Almost 40% of road in Indonesia are damaged. To obtain the maximum result of road improvement, the surface course (asphalt pavement) of the damaged road should be removed. Considering the number of quarries of road pavement materials are limited in the future and the costs are getting more expensive, it is important to do research on recycling asphalt pavement material as road base material. The objective of this research is to examine the use of asphalt pavement removal as road base material. Laboratory test was conducted to investigate the properties of the removal road asphalt pavement and then compared with specification of road base material Bina Marga. The tests include abrasion test, particles size distribution, density and California Bearing Ratio (CBR). Research was initiated by investigating the removal of asphalt pavement maerial, followed by removal of asphalt pavement material + new aggregate, and the addition of 0.5%, 1%, 1.5%, 2% and 2.5% portland cement to the mixture of removal of asphalt pavement material and new aggregate. The result shows that adding 0.5% and 2.5% portland cement to the aggregate mixture can improve the CBR of aggregate mixture by 36% and 94%, which means the mixture of aggregate can be used as sub base and base material of road.